Wine making from fruit discards - Cortes, Monina Suson 1932- ([Quezon City s.n.], 1974)
This study serves as an instructional material on the use of santol peels and pineapple "eyes" in wine making and the subsequent analysis of the product.
Thesis (M.A.T.Chemistry)--University of the Philippines.
Keywords: Wine and wine making; Fruit wines